PENDIDIKAN AKHLAK PADA ANAK MI/SD MELALUI MEDIA LAGU GUBAHAN - Dian Nurul Fajriyah (Prodi PGMI STPI Bina Insan Mulia Yogyakarta, 2018)
Learning moral education in MI/SD still emphasizes the intellectual aspect, namely the development of calistung (reading, writing and arithmetic). Moral education needs to get a better portion, learning moral education can be taught not only through the media of stories or memorization but can also be done in direct practice. The method used to convey moral education to children is certainly different from the method used for adults. One of the right methods is to use the singing method which can be applied in aspects of child development. The aims of this study were: (1) to describe the application of moral education through the media of composed songs (2) to describe the effectiveness of moral education through the media of composed songs. This study used qualitative research methods. The theory used is the theory of Jamulus, singing activity is an activity in which we produce sounds in an orderly and rhythmic manner, either accompanied by music or without musical accompaniment. Singing is different from talking. Singing requires certain techniques while speaking without the need to use certain techniques. The results of the study show (1) the application of learning through the media of composed songs includes the habit of singing every day, listening to Islamic songs for children, and integrating songs according to the theme. (2) The effectiveness of teaching moral education with media composed songs can be said to be effective. This is due to changes in attitudes, as well as children's understanding and behavior which are seen significantly between before and after the research action is taken.